Konseling Kids: Meningkatkan Aspek Sosial Emosional Anak dengan Permainan Tradisional Jamuran di TK Aisyiyah 1 Gumpang - Nurul Ilmi Azizah, Annafi; Zahra Alfiah, Hasna; Niken Azida, Fauziyyah; Azra Istiadah, Jelena; Nur Azzura, Ellyana; Nur Hidayanti, Aryani; Bidri Chaerani, Ishwar; Viarani Putri, Indah (Mulya Literasi Publishing, 2024)
Traditional games play an important role in introducing local culture to children while also supporting their social and emotional development. This article reviews community service at TK Aisyiyah 1 Gumpang, which uses the traditional game Jamuran as a counseling medium to enhance the social-emotional skills of early childhood. This game was chosen because it can encourage social interaction, cooperation, and empathy, while also preserving local culture. The stages of this PkM activity are divided into three: pre-activity involving permits and observations, implementation of activities with Jamuran movement and song training, and post-activity evaluation. The results show that the Jamuran game is effective in building social interaction, reducing solitary behavior, and enhancing children's cooperation. In addition, this game serves as an enjoyable educational tool to instill values such as cooperation and anti-bullying. This article emphasizes the importance of a traditional game-based approach in supporting the holistic development of early childhood, both physically, mentally, and socio-emotionally.